Pengaruh permainan memorize card terhadap hasil belajar kognitif siswa sekolah dasar dalam pembelajaran Penjas pada materi sepak bola - Assidiq, Muhamad Thoriq; Ali Rahman, Aam; Saptani, Entan (IKIP Siliwangi, 2025)
Abstract This study aims to examine the impact of the Memorize Card game on students' cognitive learning outcomes in Physical Education, specifically on football. Preliminary surveys conducted in several elementary schools in Situraja District revealed low student understanding of basic football concepts. This research uses a quantitative experimental method with a Quasi-Experimental Design (Non-Equivalent Pre-Test and Post-Test Control Group Design). The subjects were divided into two groups: the experimental group at SDN Malaka and the control group at SDN Bakan Bandung. Data analysis using an independent samples t-test revealed a significant difference between the posttest scores of both groups, with a significance value (Sig. 2-tailed) of 0.000. This indicates that the Memorize Card game positively influences students’ cognitive learning outcomes. The N-gain analysis supports this, with the experimental group scoring 73.01% (high category) and the control group scoring only 11.10% (low category). Student responses to the game were highly positive, with 97.05% reporting that it helped them understand the material more easily and increased their engagement during learning. Therefore, the Memorize Card game has a positive impact and can improve students' cognitive learning outcomes and motivation in football lessons. Keywords: Memorize Card, Cognitive Learning Outcomes, Football Abstrak Penelitian ini bertujuan untuk menguji pengaruh permainan Memorize Card terhadap hasil belajar kognitif siswa dalam pembelajaran Pendidikan Jasmani, khususnya materi sepak bola. Hasil prasurvei di beberapa sekolah dasar di Kecamatan Situraja menunjukkan rendahnya pemahaman siswa terhadap konsep dasar permainan sepak bola. Penelitian ini menggunakan metode eksperimen kuantitatif dengan desain Quasi Experimental Design (Non Equivalent Pre-Test and Post-Test Control Group Design). Subjek penelitian terdiri dari dua kelompok: kelas eksperimen di SDN Malaka dan kelas kontrol di SDN Bakan Bandung. Hasil analisis data menggunakan uji-t dua sampel independen menunjukkan perbedaan yang signifikan antara hasil posttest kedua kelompok, dengan nilai signifikansi (Sig. 2-tailed) sebesar 0,000. Hal ini menunjukkan bahwa Memorize Card berpengaruh positif terhadap peningkatan hasil belajar kognitif siswa. Hasil tersebut diperkuat dengan analisis N-gain, di mana kelas eksperimen memperoleh skor sebesar 73,01% (kategori tinggi), sedangkan kelas kontrol hanya 11,10% (kategori rendah). Respon siswa terhadap permainan ini juga sangat positif, dengan 97,05% siswa menyatakan lebih mudah memahami materi dan lebih terlibat dalam pembelajaran. Dengan demikian, Memorize Card berpengaruh positif dan dapat meningkatkan hasil belajar kognitif serta motivasi siswa pada materi sepak bola. Kata Kunci : Memorize Card, Hasil Belajar Kognitif, Sepak bola.